FINDING CONNECTION BETWEEN READING AND WRITING - Ista Maharsi (Jurnal Cakrawala Pendidikan, 2016)
This paper is aimed to describe the implementation of extensive reading program, reveal students’ vocabulary size before and after the program, and explore students’ perception on extensive reading program and the use of Cartoon Story Maker to create cartoon stories. There were 17 students participating in this study. Data were collected from pre-test, post-test, observations, focus group discussions, and interviews. Findings show that students’ vocabulary level rises by averagely 1.135 words. Students’ perception on reading activities and their reading preferences change. More interestingly, the extensive reading program has given them joyful reading experiences and encouraged them to read more. Reading logbooks function as scaffolding for vocabulary learning and sentence structure awareness. In addition, Cartoon Story Maker is perceived as the tool to develop imagination into stories built up from their previous reading experiences. This study indicates that there is a connection between reading and writing through several aspects that establish reading and writing skills. The cartoon stories are inspired by the stories they read, the vocabulary they learned, the retold plots, and there is an artful blend of imagination and creativity. Keywords: extensive reading, cartoon story maker, creativity Makalah ini bertujuan untuk menggambarkan tentang pelaksanaan program Extensive Reading (membaca luas), menemukan jumlah kosakata siswa, dan mendeskripsikan persepsi siswa terhadap program membaca luas serta penggunaan Cartoon Story Maker untuk membuat cerita kartun. Ada 17 siswa yang berpartisipasi dalam penelitian ini. Data diambil dari pre-tes, pos-tes, observasi, diskusi kelompok, dan wawancara. Hasil penelitian ini menunjukkan bahwa tingkat kosakata siswa meningkat rata-rata 1.135 kata. Persepsi siswa terhadap kegiatan membaca dan kegemaran membaca berubah. Yang lebih menarik lagi adalah bahwa program membaca luas ini telah memberi siswa pengalaman membaca yang menyenangkan dan memotivasi mereka untuk membaca lebih banyak. Buku kontrol membaca berfungsi sebagai pelajaran berulang tentang kosakata dan struktur kalimat. Cartoon Story Maker diasumsikan sebagai medium untuk menuangkan imaginasi cerita yang mereka dapatkan dari membaca luas. Penelitian ini mengindikasikan bahwa ada hubungan antara membaca dan menulis yang dibangun melalui pengalaman membaca sebelumnya. Cerita kartun terinspirasi oleh cerita dari buku yang mereka baca, kosakata yang mereka pelajari, alur cerita yang dikisahkan ulang, serta penggabungan imaginasi dan kreativitas. Kata kunci: membaca luas, cartoon story maker, kreatifitas